Business Cycles and Workers' Remittances : How Do Migrant Workers Respond to Cyclical Movements of GDP At Home? - Sayan, Serdar (IMF Working Papers; Working Paper, 2006)
Workers' remittances are often argued to have a tendency to move countercyclically with the GDP in recipient countries since migrant workers are expected to remit more during down cycles of economic activity back home. Yet, how much to remit is a complex decision involving other factors, and different variables driving remittance behavior are differently affected by the state of economic activity over the business cycle. This paper investigates the behavior of workers' remittances flows into 12 developing countries over their respective business cycles during 1976-2003 and finds that countercyclicality of receipts is not commonly observed across these countries.